Customers' perception study towards modular housing system in Sarawak / Mohd Nazri Hj Ismail - Hj Ismail, Mohd Nazri (2000)
A study was carried out to gather the opinions and perceptions of perspective customers towards the modular housing system. In the course of the study, the researcher has chosen CMS Modular Housing Sdn. Bhd. to be the model company which pioneered the modular housing system project in Sarawak. CMS Modular Housing Sdn. Bhd. was incorporated in July 1998 and has started its first commercial production in October 1998. A factory was set up to manufacture pre-fabricated housing modules and components for Cahaya Mata Sarawak Berhad (CMSB ) group's housing projects, and other private developers and builders. Bandar Samariang Housing Project is one of the projects that involves the construction of modular housing system. Presently, it involves the construction of 2,500 units two bedroom type low cost houses with the price of RM 32,000. The sales of those houses is undertaken by PERUMAHAN and so far the sales of the house is very slow. From the study, the real customers' perception towards modular house was identified and through this the company might used it to improve their strengths and weaknesses. In this study several recommendation being proposed to enhance the marketing strategy of CMS Modular Housing Sdn. Bhd. which is detailed out in Chapter 6 of the paper. However, this was only an academic project.